Weaving a Path from Waste to Value: Exploring Fashion Industry Business Models and the Circular Economy - Kerli Kant Hvass (Copenhagen Business School (CBS), 2016)
This dissertation examines post-consumer textile waste from the fashion industry's perspective, and addresses how business model innovation can facilitate reuse and recycling of garments and a transition towards a circular economy of fashion. Focusing on the emerging reuse and recycling practices of fashion brands the study builds upon one explorative and two in-depth case studies of industry pioneers and their endeavors of integrating reuse and recycling activities in their business models. Theoretically the study rests on business models, business model innovation for sustainability and circular economy. The study seeks to provide a unique contribution as it synthesizes the theoretical and empirical insights from the field of business model innovation and circular economy in the context of post-consumer textile waste. By highlighting and extending the idea of business model innovation for circular economy it makes a justification that product end-of-life phases require attention and can include new value propositions that companies can create, deliver and capture. This dissertation contains three articles, each of which contributes to an improved understanding of post-consumer textile waste management in the context of the fashion industry and its related opportunities and challenges. The findings cover both broad industry-level and more specific company-level discoveries. The industry-level findings provide a general understanding of existing practices among fashion companies while the company specific findings identify key issues and challenges of integrating a product's end-of-life aspects in an existing business model. Collectively, the findings demonstrate that end-of-life management of products is an emerging field among fashion companies and used garments can provide new value propositions for fashion brands. The findings also illustrate that the field is in its infancy and lacks best practices within business models, supply chain infrastructure, technological solutions and consumer engagement. Transition towards a circular economy implies full systemic change, and innovation not only in business models, but also in technologies, society, policies and finance methods as well as consumer behavior. None of these aspects can work in isolation and require that different stakeholders work in tandem.
hdl:10398/9282
Keywords: 650